Contemplating the Bibliometric Data Onto Sepsis and Gut Microbiome: Mapping Trends, Collaborations, and Global Contributions - Zhang Li; Wang Yi; Li Ping; Li Xiang; Yu Xiangyou (Postępy Mikrobiologii)
Sepsis is a leading cause of hospital mortality, closely linked to gut dysfunction and dysbiosis. The gut microbiome’s role in sepsis pathogenesis and progression necessitates a comprehensive bibliometric analysis to elucidate current research trends. Utilizing the Science Citation Index Expanded (SCI-E) database, literature was systematically retrieved using the terms: sepsis AND (“gut” OR “gastrointestinal”) AND (“microbiome” OR “microbiota” OR “microflora” OR “bacillus”). After data refinement and duplicate removal, 2485 articles were included for statistical analysis using R software’s bibliometric package, with Excel used to visualize publication trends. Findings demonstrate a progressive annual increase in published studies and citations. The United States and France emerged as primary contributors, exhibiting extensive international collaboration. Among leading institutions, the University of California ranked highest in research output, while Wiersinga WJ from the University of Amsterdam led in publication volume and collaborative networks. Research predominantly focuses on critical care medicine, immunology, and microbiology, with keywords such as sepsis, microbiome, microbiota, and microflora recurring. Current trends indicate a growing focus on the relationship between sepsis and gut microbiome dynamics, with a notable gap in evidence-based clinical applications. The prominence of the United States in the field underscores the need for welldesigned clinical trials and prospective cohort studies to advance therapeutic strategies. Strengthening global collaboration, particularly through increased involvement of Chinese researchers, is crucial for a comprehensive understanding and future advancements in this complex and evolving field.